Association between Bubble Tea Consumption and Prevalence of Acne Vulgaris - Devina Subagio; Asih Budiastuti; Yulian Ludovicus Aryoko Widodo; Puguh Riyanto (Cermin Dunia Kedokteran, 2021)
Introduction: Acne vulgaris (AV) is one of the most common skin disorders among youth. A cross-sectional study was conducted to analyze the association between bubble tea consumption and the prevalence of acne vulgaris among medical students. Method: Subjects were obtained from consecutive sampling. There were 91 eligible subjects meeting inclusion criteria. Data was collected using questionnaires. Examinations were through the observation of photographs of lesions. Chi-square analysis was conducted at a 95% confidence interval (p<0.05). Results: Data were collected from 91 medical students with a mean age of 19.62+0.98-year-old. The prevalence of acne was 58.2%, mainly at the age of 20 (37.7%). There is a significant association between consumption of bubble tea and the prevalence of AV (p<0.001). Conclusion: Bubble tea consumption is associated with the prevalence of acne vulgaris. Pendahuluan: Akne vulgaris merupakan salah satu penyakit kulit yang umum dialami pada dewasa muda. Metode: Penelitian observasional cross-sectional untuk mengetahui asosiasi konsumsi bubble tea dengan kejadian akne vulgaris. Sampel diambil dengan metode consecutive sampling menghasilkan 91 mahasiswa yang memenuhi kriteria inklusi dan eksklusi. Pengambilan data primer dengan kuesioner. Pemeriksaan fisik observasi kulit responden dengan foto. Analisis data menggunakan uji Chi-Square dengan tingkat kemaknaan p<0,05. Hasil: Angka kejadian akne vulgaris adalah 58,2%, dengan rata-rata usia 19,62+0,98; usia terbanyak penderita adalah 20 tahun (37,7%). Terdapat asosiasi bermakna antara konsumsi bubble tea dan kejadian akne vulgaris (p<0,001). Simpulan: Penelitian ini menunjukkan hubungan bermakna antara konsumsi bubble tea dan kejadian akne vulgaris.